2012
DOI: 10.1177/0091270011403313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild and Moderate Hepatic Impairment on the Pharmacokinetics and Safety of Carisbamate

Abstract: This open-label, parallel-group study was designed to characterize the pharmacokinetics (PK) of carisbamate in participants with mild or moderate hepatic impairment versus those with normal hepatic function. Healthy (n = 10) and hepatic-impaired (n = 20) participants received a single 200-mg oral dose of carisbamate. Serial PK blood samples were collected up to 120 hours postdose. A modest increase in mean area under the plasma concentration-time curve from 0 to infinity (AUC(∞)) was observed for the mild impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Carisbamate (S-2-O-carbamoyl-1-o-chlorophenyl-ethanol) is an investigational neuromodulatory agent, initially developed from SK Biopharmaceuticals (Seongnam, Korea) for antiepileptic treatment [ 1 2 3 4 5 6 ]. Although the exact mechanism of action for carisbamate is not known, carisbamate has been studied for the treatment of epilepsy, essential tremor and migraine [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carisbamate (S-2-O-carbamoyl-1-o-chlorophenyl-ethanol) is an investigational neuromodulatory agent, initially developed from SK Biopharmaceuticals (Seongnam, Korea) for antiepileptic treatment [ 1 2 3 4 5 6 ]. Although the exact mechanism of action for carisbamate is not known, carisbamate has been studied for the treatment of epilepsy, essential tremor and migraine [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carisbamate (S-2-O-carbamoyl-1-o-chlorophenyl-ethanol) is an investigational neuromodulatory agent, initially developed from SK Biopharmaceuticals (Seongnam, Korea) for antiepileptic treatment [ 1 2 3 4 5 6 ]. Although the exact mechanism of action for carisbamate is not known, carisbamate has been studied for the treatment of epilepsy, essential tremor and migraine [ 4 5 ]. In phase I clinical trials to healthy subjects, carisbamate has shown linear pharmacokinetics at doses of 100 to 1,500 mg, high oral bioavailability (F) of > 95% and a low oral clearance (CL/F) of 3.4–4.2 L/h, equaling < 5% of liver blood flow [ 1 2 7 ].…”
Section: Introductionmentioning
confidence: 99%